Dynamics of socio-cultural potential of the educational complex of the region in the context of innovative development - A. A. Lezhebokov; E. A. Sergodeeva; A. V. Bashtovaya (Вестник Северо-Кавказского федерального университета, 2023)
This work has as its main goal to reveal the influence of the educational complex of the region on the processes of modernization and innovative development of the territory. The perspective of this study is based on the analysis of the dynamics of the socio-cultural potential of the education system in the Karachay-Cherkess Republic as an outsider region in terms of economic development. The methodology of the research is based on the application of the anthroposocietal approach as a modification of the sociocultural direction. In the process of studying the socio-cultural potential of the education system, it was determined that there is no relationship between the level of education of the population of the region and the indicators of the innovative development of the territory. The dominance of traditional attitudes in the worldview orientations of the population and the high level of non-legal practices leads to a situation of securing a formal-normative status for a high level of education of an individual. The results of the study make it possible to develop a set of measures to improve regional development programs using the potential of the education system as a factor that largely determines the dynamics of the modernization process.